Building a Resilient Village Based on Entrepreneurship and Digital Literacy Through Strengthening Entrepreneurial Mindset - Andika Isma; Muhammad Rakib; Hajar Dewantara; Andi Anggi Kemalasari; Andi Naila Quin Azisah Alisyahbana; Sitti Hajerah Hasyim; Muhammad Jufri (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
Strengthening the economic potential of rural areas is one of the government's village empowerment programs. However, it is known that there are still problems related to the low competitiveness of rural areas, both in terms of human resources and the ability to produce commodities with added value. The Sokkolia Village Government, young people, and community leaders play a crucial role in boosting the resilience of rural communities. The tripartite cooperation model of Bumdes, Industry, and Campus is expected to address these two problems. The Campus can help in conducting research on potential and formulating innovative designs, while Industry can assist in terms of technology and market access. This training aims to help equip the Sokkolia Village community with entrepreneurial literacy and digital literacy to optimize the potential of the village and local economic growth. Empowering the community through entrepreneurship and digital literacy is expected to create an ecosystem that supports local economic growth and contributes positively to sustainable development at the village level. The training that has been conducted shows high levels of participation and motivation among partners. Based on the results of the training, partners' understanding of entrepreneurship and digital literacy has increased. This is expected to make Sokkolia Village partners adaptable and able to utilize digital technology to improve their overall well-being.